Management of chronic pain secondary to temporomandibular disorders: a systematic review and network meta-analysis of randomised trials (BMJ (Online), 2024)
In this paper by Yao and colleagues (BMJ 2023;383:e076226, doi:10.1136/bmj-2023-076226, published 15 December 2023), the legends to the network plots (figures 2, 4, and 5) have been expanded to clarify what the plots show.